E-Voting Application Interface Design Based on User Emotional Preferences Using Kansei - Abdurrohman, Muhammad; Aedah, Abd Rahman; Sabar, Muhamad (2024)
The increasing use of technology has made people accustomed to using it, especially in the digital age. In the field of politics, information technology is used to support the holding of elections remotely through the internet. The appearance and design of the user interface of an e-voting application is a crucial factor in determining its success, as the display design can affect user psychology when using it. A well-designed interface can improve the user experience and increase the likelihood of successful adoption and usage of the e-voting system. On the other hand, a poorly designed interface can create confusion and frustration for users, leading to a decrease in trust and adoption of the system. This research has allowed for a deeper understanding of the emotional and psychological factors that influence people's perceptions and interactions with the e-voting application. By gathering and analyzing data about users' emotional feelings through the use of Kansei words and statistical multivariate analysis, the researchers were able to identify the key emotional and psychological factors that should be considered when designing the user interface, these findings can be used to inform the design of the e-voting application in order to create a more appealing and satisfying user experience